Excessive Body Weight as a Determinant of Quality of Life - Skoczylas, Alicja; Siudziński, Paweł; Łyko, Mateusz; Tomaszewska, Wiktoria; Pala, Katarzyna; Podlasiewicz, Wiktoria; Golińska, Maria; Kurasz, Jakub; Maj, Wojciech; Dudziak, Piotr; Nowak, Anna (Quality in Sport, 2025)
Introduction and objective. This article aims to discuss the issue of excessive body weight based on available literature. It highlights the physical and psychosocial consequences of obesity and addresses the topic of weight reduction. Review methods. Bibliographic material was retrieved from PubMed and Google Scholar using terms related to obesity, overweight, and quality of life. Forty-six articles published between 2015 and 2024 were selected. Conclusions. Obesity is a source of numerous somatic and psychosocial complications. The article shows the negative impact of these consequences on quality of life. One of the main goals of obesity treatment is to improve quality of life. Therefore, the article describes manner to reduce body weight, sources of motivation and adversity on the treatment path and explores the topic of psychological support in obesity treatment.